A micromechanics approach for effective elastic properties of nano-composites with energetic surfaces/interfaces. (1st January 2017) - Koutsawa, Yao; Tiem, Sonnou; Yu, Wenbin; Addiego, Frédéric; Giunta, Gaetano
Abstract: The mechanics of structure genome is generalized to model nanocomposites taking into account the surfaces/interfaces stress effect at nano-scale. This full field micromechanics approach is applied to predict the effective properties of composites containing nano-inhomogeneities. Examples of binary composite materials, fiber reinforced composite materials and particle reinforced composite materials are used to demonstrate the robustness and accuracy of this micromechanics theory with surfaces/interfaces effects. The size-dependency of the overall elastic moduli shows the importance of energetic surfaces/interfaces in modeling the mechanical behavior of nano-scale composite materials. The proposed micromechanics approach is versatile enough to be applied for estimating the effective elastic properties of many nano-composite materials.